The O-specific polysaccharide lyase from the phage LKA1 tailspike reduces Pseudomonas virulence. Issue 1 (December 2017) - Olszak, Tomasz; Shneider, Mikhail; Latka, Agnieszka; Maciejewska, Barbara; Browning, Christopher; Sycheva, Lada; Cornelissen, Anneleen; Danis-Wlodarczyk, Katarzyna; Senchenkova, Sofya; Shashkov, Alexander; Gula, Grzegorz; Arabski, Michal; et al.
Abstract Pseudomonas phage LKA1 of the subfamilyAutographivirinae encodes a tailspike protein (LKA1gp49) which binds and cleaves B-band LPS (O-specific antigen, OSA) ofPseudomonas aeruginosa PAO1. The crystal structure of LKA1gp49 catalytic domain consists of a beta-helix, an insertion domain and a C-terminal discoidin-like domain. The putative substrate binding and processing site is located on the face of the beta-helix whereas the C-terminal domain is likely involved in carbohydrates binding. NMR spectroscopy and mass spectrometry analyses of degraded LPS (OSA) fragments show an O5 serotype-specific polysaccharide lyase specificity. LKA1gp49 reduces virulence in an in vivo Galleria mellonella infection model and sensitizesP. aeruginosa to serum complement activity. This enzyme causes biofilm degradation and does not affect the activity of ciprofloxacin and gentamicin. This is the first comprehensive report on LPS-degrading lyase derived from aPseudomonas phage. Biological properties reveal a potential towards its applications in antimicrobial design and as a microbiological or biotechnological tool.